What is the relationship between outdoor play breaks & no play breaks on postural balance? : A Systematic Review - Campbell-Pierre, Daryl; Rhea , Debbie; Baker, Kathy (Journal of Health and Physical Literacy, 2022)
Background The growing trend of sedentary behaviors in children has been linked to less play and physical activity opportunities. The rising concern of children moving less daily is the development of postural balance deficiencies. These deficiencies have been shown to decrease motor competence and increase non-fatal falls and injuries at earlier ages. Therefore, a better understanding of play interventions and their impact on a child’s postural balance may improve motor competence and decline non-fatal falls. Methods Three Electronic databases (PubMed, CINHAL & Google Scholar) and trial registers were searched for published and unpublished studies. All articles from the database inception to the present, published in English, were included. Findings Out of 286 articles identified, two studies met the inclusion criteria. Both articles were cross-sectional studies that evaluated outdoor play breaks versus no play breaks and postural balance among 3–14-year-old children. The outdoor play exposure intervention was described in both studies as outdoor recess, but two different motor coordination measurement tools were used to assess postural balance. Conclusion: Despite the limited evidence, the findings suggested that outdoor physical activity positively impacts postural balance and functional motor skills (FMS).